O privire critică asupra dispozițiilor constituționale privind proprietatea publică [Articol] - Guţu, Gheorghe (CEP USM, 2020)
There are now in Republic of Moldova two forms of property: public and private property. The state protects property. Public property belongs to the state or administrative-territorial units. Lands may belong to public or private domain. The assets that belong to public domain are: inalienable, indefeasible and imperceptible.
A CRITICAL OVERVIEW OF CONSTITUTIONAL PROVISIONS CONCERNING PUBLIC PROPERTY
Keywords: proprietate publică; bunuri; protecția proprietății publice